PENGARUH PERSONAL SELLING, DIGITAL MARKETING, DAN PERCEIVED VALUE TERHADAP KEPUASAN KONSUMEN PRODUK SKINCARE WARDAH DI KOTA BATAM - Messy Juliaya Saputri; Wasiman (SCIENTIA JOURNAL, 2024)
The aim of this research is to determine the influence of personal selling, digital marketing, and perceived value on consumer satisfaction with Wardah skincare products in Batam City. This research is descriptive in nature and uses a quantitative approach to collect and analyze data. The population of this study was Wardah skincare users in Batam City in 2024. To determine the sample size, the Lameshow formula was used to obtain a total of 100 respondents selected through purposive sampling. In this research, various tests were carried out, including data quality tests, classical assumption tests, influence tests, and hypothesis tests. The results of multiple linear regression analysis show that personal selling contributes 9.6% to consumer satisfaction. Digital marketing has an influence with a contribution of 27.6% to consumer satisfaction. Perceived value contributes 20.9% to consumer satisfaction. Analysis of the coefficient of determination (R2) shows that the overall variance in consumer satisfaction can be explained by personal selling, digital marketing and perceived value with a total contribution of 80.3%. The results of the t test and F test show that personal selling, digital marketing, and perceived value have a positive and significant influence both partially and collectively on consumer satisfaction.